An investigation of ultrasound methods for the assessment of sex and age from intact human teeth - Robin N. M. Feeney (Dental Anthropology Association, 2005)
Determining sex and age in human remains is necessary to achieve positive identification of individuals in forensic settings, and to provide data required for demographic analyses in archaeological samples. Due to their denser mineralization, teeth may be better preserved than other skeletal elements, which are often fragmentary and poorly preserved. This work is the first to investigate the use of ultrasound methods to accurately, objectively, and non-destructively assess sex and estimate age of human skeletal remains from intact teeth. An ultrasound imaging system using pulse-echo technique and nominal frequency (3.5 MHz) longitudinal waves was developed for application on teeth. Mechanical and acoustic properties of teeth were examined to explore their relationship with the interaction of ultrasound wave propagation. Experiments were conducted to determine differences in wave propagation in teeth from individuals of different ages and sex, both permanent and deciduous. Consistent differences in integral acoustic response patterns in the different teeth were found. It is concluded that pulse-echo ultrasound is a viable non-destructive technique to yield integral acoustic characteristic properties of teeth, potentially useful for assessing sex and estimating age, and resolving minimum numbers of individuals from commingled and scattered remains. Information developed from this study will be significant to future research insofar as it introduces a new potential method that is nondestructive, fast, and easy to administer in situ.